LAW DEVELOPMENT OF WAQF AL-NUQUD (CASH WAQF) TOWARDS ELECTRONIC WAQF (E-WAQF) BASED ON PUBLIC WELFARE - Ong Argo Victoria; Russel Ong (Universitas Islam Sultan Agung, 2019)
The modern era is identified with the era of the digital society. Every human activity will be driven through a series of digital technology. For example everything is electronic through the identification number Electronic Identity Card (E-ID), Card payment toll road electronic (E-Toll), ATM, PIN (Personal Identification number), etc. all using the digital system. No exception waqf management innovation has also been happening in Islamic countries including Kuwait, Qatar, Emirates, Jordan, Saudi Arabia, Egypt, Turkey, Bangladesh, Malaysia, Singapore, and even Europe and America. Among the endowments with a paradigm shift arrangements progressive approach fairly fundamental law, among others, first, in the case of an asset in waqf no longer confined to immovable property, but also against movable property. Evidence used to reinforce this view, as formulated in Article 16 Paragraph (1) of Law No. 41 of 2004 on endowments, which reads â€œ treasure be in waqf is immovable and moving objectsâ€. This article aims to make an overview on the developing of law on waqf al-nuqud towards electronic waqf (e-waqf) to realize the public welfare.Keywords: Law Development; Waqf Al-nuqud; E-Waqf; Welfare.